Combining Prenatal Yoga and Self-Hypnosis as Effective Intervention to Reduce Blood Pressure of Pre-Eclampsia Pregnant Women - Anisak, Siti; Irawati, Deasy; Wayanti, Sri (STIKes Patria Husada Blitar, 2025)
Pre-eclampsia (PE) is a significant cause of maternal and fetal morbidity and mortality. PE requires intervention to prevent it from developing into severe pre-eclampsia or eclampsia. One of the non-pharmacological therapies for PE that has not been widely used is prenatal yoga and self-hypnosis. This research aimed to determine the effect of combining prenatal yoga and self-hypnosis on decreasing blood pressure in pregnant women with PE. The method was quasi-experimental, with a pretest-posttest and a control group design. The population was all pregnant women with PE in 5 health centers in Bangkalan district from May to August 2024. The sampling technique used simple random sampling with the Federer formula, with a total sample of 32 people, 16 in each group. The research instruments used calibrated digital tension meters and SOPs for prenatal yoga and self-hypnosis. The results of the Wilcoxon analysis test showed that prenatal yoga and self-hypnosis effectively reduced blood pressure in pregnant women with pre-eclampsia with a p-value of 0.000 (p <0.05). Yoga and self-hypnosis are effective in lowering blood pressure by increasing the physical, mental, and spiritual strength of the mother in dealing with pregnancy with PE.